Databases and other sources of information in systematic reviews: practical recommendations - Araújo, Wánderson Cássio Oliveira; Lopes, Fernanda Machado; Dias, Natália Martins; Bousfield, Andréa Barbará da Silva; Silva, Mariana Luíza Becker da; Steil, Andrea Valéria (Informação em Pauta, 2024)
Bibliographic databases are the main source of information for identifying and retrieving primary studies to be synthesized in systematic reviews (SR). Based on the analysis of the information sources used in 305 SR in Psychology, the aim of this article is to explain how the information sources have been reported in SR in Psychology and to present practical solutions for the identified gaps and inconsistencies. The article presents a classification of bibliographic academic information sources, defines a bibliographic database and demonstrates how to correctly name information sources in SR. It also discusses the number of bases in SR, the construction of search strategies, the use of controlled vocabulary and the explosion in databases. Finally, the article discusses the issue of gray literature, the use of complementary sources, the issue of the regionality of information sources and the role of the librarian in the SR. It is hoped that the issues discussed and the practical recommendations in this article will contribute to the improvement of the SR carried out by researchers in all areas of knowledge.